Oxygen-dependent regulation of permeability in low resistance intestinal epithelial cells infected with Giardia lamblia - Souza, Juliana Bizarri; Tsantarlis, Katherine; Tonelli, Renata Rosito (Experimental parasitology, 2022)
Intestinal epithelial cells (IECs) reside in a highly anaerobic environment that is subject to daily fluctuations in partial oxygen pressure (pO2), depending on intestinal tissue perfusion. This condition, known as physiological hypoxia, has a major impact on the maintenance of gut homeostasis, such as effects on the integrity and function of the intestinal epithelial barrier. Giardia lamblia is a microaerophilic protozoan parasite that infects and colonizes the small intestine of its host, causing watery diarrhea. The disease, known as giardiasis, is associated with enhanced intestinal permeability and disruption or reorganization of tight junction (TJ) proteins between IECs. Given the central role of oxygen in gut homeostasis, in this study, we aimed to evaluate whether pO2 affects intestinal permeability (flux of ions and macromolecules) and TJ protein expression in human IECs during G. lamblia infection. Using human cell lines HuTu-80 and Caco-2 as models of “loose” (low resistance) and “tight” (high resistance) intestines, respectively, we elucidated that low pO2 drives intestinal barrier dysfunction in IECs infected with trophozoites through dephosphorylation of protein kinase C (PKC α/β II). Additionally, we demonstrated that IECs infected with trophozoites in the presence of a pharmacological PKC activator (phorbol 12-myristate 13-acetate) partially restored the barrier function, which was correlated with increased protein expression levels of zonula occludens (ZO)-2 and occludin. Collectively, these results support the emerging theory that molecular oxygen impacts gut homeostasis during Giardia infection via direct host signaling pathways. These findings further our knowledge regarding Giardia-host interactions and the pathophysiological mechanisms of human giardiasis. [Display omitted] •HuTu-80 cells form monolayers of lower TEER compared to Caco-2 cells.•G. iardia infection increases intestinal permeability to ions in HuTu-80.•Reduction on pO2 exacerbates intestinal permeability of HuTu-80 cells infected with Giardia.•PKCα/β II dephosphorylation mediates barrier dysfunction in HuTu-80 cell under anaerobiosis and infected with Giardia.•Activation of PKCs restores barrier function in HuTu-80 infected -cells under anaerobiosis and increases ZO-2/occludin protein.